The Liability of PPAT Notary against Fraud Crimes in Carrying Out His Position - Chaniago, Alkaf (Jurnal Konstatering, 2022)
This writing aims to understand and analyze the process of examining a Notary who is suspected of committing a criminal act of fraud and the Notary's responsibility for criminal acts of fraud in carrying out his position. The research method using the problem approach that will be used in this thesis is a normative juridical approach. The results of the study show that the process of examining a Notary who is suspected of committing a crime of fraud is carried out in accordance with statutory regulations, namely Article 66 of Act No. 2 of 2014 concerning Amendments to Act No. 30 of 2004 concerning the Position of Notary, Regulation of the Minister of Law and Rights Human Rights Number M.03.HT.03.10 of 2007 which specifically regulates the taking of minutes and summons of a Notary (Permen 03/2007). Notary Bachtiar did not report his case to the Pekalongan City Regional Management Council, so Bachtiar did not receive legal assistance from the MPD. This was confirmed by the investigators that during the examination at the investigative level and at the Attorney General's Office, Notary Bachtiar was not accompanied by the MPD. However, at the time of the trial, he was accompanied by an expert, namely Notary Prof.Dr. Widhi Handoko, SH, M.Kn. The notary is criminally responsible when in the process of proving that the notary is proven to have committed a crime or mistake. The Law on Notary Office and the notary's code of ethics do not regulate the responsibility of a notary criminally against the deed he made if it is proven that he has violated the criminal law.Keywords: Accountability; Fraud; Notary; Public.